Деякі особливості перекладів Григорія Кочура англійської поезії - Янюк, Я. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the peculiarities of translation of English poems made by Ukrainian poet Hryhoriy Kochur, the preservation and loss of their poetic potential in translational transformation. The most significant problems which take place in the process of translation and the way of their solving are analyzed. Attention is also paid to the ways of realization of the author’s ideas in translated poetry.